Purity Analysis of Sesame Oil Extracted from Sesamum indicum L. Using the ATR-FTIR Method - Mahendra, Muhammad Reza; Salamah, Nina; Guntarti, Any (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Sesame seeds (Sesamum indicum L.) are a plant that produces the most important and oldest oil known to man. Apart from being rich in nutrients, sesame consists of important functional components such as sesamin, sesamolin, sesamol, sesaminol, sesamolin phenol, and other lignan-like active ingredients and can trigger the motive to produce sesame oil by adulteration in order to achieve market desires. The aim of this research is to identify the purity of sesame oil and analyze it using the ATR-FTIR method to detect and prevent counterfeiting. Testing the characteristics of sesame oil can be adjusted to the quality requirements that have been set, one of which is the Indonesian National Standard (SNI) so that the quality of sesame oil circulating on the market is guaranteed. This research is non-experimental research. Sesame seed oil resulting from pressing is based on the test requirements of SNI 01-4468-1998 including the physico-chemical properties test. The results of the sesame seed oil profile are that the sesame seed oil extraction yield is 29.265%, the sesame oil is bright yellow in color, has a distinctive smell, specific gravity (20oC) 0.9237± 0.0057, refractive index 1.4702 ± 0.0005, peroxide value 2 ± 0.0577 meqO2/Kg, iodine value 107.1 ± 0.5773, and acid number 0.224 ± 0.0577. Based on the research results, it can be concluded that the pressed sesame seed oil has met the requirements of the SNI 01-4468-1998 test, and from the functional groups that appear in the ATR-FTIR it can be concluded that the pressed sesame oil contains methyl ester group compounds.